1975
DOI: 10.1128/jvi.16.1.184-191.1975
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of prophage mutants of the defective Bacillus subtilis bacteriophage PBSX

Abstract: Bacillus subtilis mutants with lesions in PBSX prophage genes have been isolated. One of these appears to be a regulatory mutant and is defective for mitomycin C-induced derepression of PBSX; the others are defective for phage capsid formation. All of the PBSX structural proteins are synthesized during induction of the capsid defective mutants; however, several of these proteins exhibit abnormal serological reactivity with anti-PBSX antiserum. The two head proteins X4 and X7 are not immunoprecipitable in a mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
16
0

Year Published

1975
1975
2006
2006

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 18 publications
3
16
0
Order By: Relevance
“…Such a postulated relationship between the genetic determinants of R-type aeruginocins and normal prophages is strengthened by the serological similarity between R-type aeruginocins and normal temperate phages of P. aeruginosa (81). The single chromosome site for the location of these determinants has its counterpart in the prophage of the defective phage PBSX of Bacillus subtilis, which also has a singular site (175). The location of the S-type aeruginocinogenicity determinant has not been determined.…”
Section: Location Of Aeruginocinogenicitymentioning
confidence: 99%
“…Such a postulated relationship between the genetic determinants of R-type aeruginocins and normal prophages is strengthened by the serological similarity between R-type aeruginocins and normal temperate phages of P. aeruginosa (81). The single chromosome site for the location of these determinants has its counterpart in the prophage of the defective phage PBSX of Bacillus subtilis, which also has a singular site (175). The location of the S-type aeruginocinogenicity determinant has not been determined.…”
Section: Location Of Aeruginocinogenicitymentioning
confidence: 99%
“…There has been considerable controversy as to exactly where the PBSX prophage is located on the genome of B. subtilis 168, and it has even been suggested that the viral genes might be scattered throughout the host chromosome. Recently, however, Garro et al (93,326) have isolated mutants of B. subtilis 168 with lesions in prophage genes controlling structural pro-teins in the virion capsid, and these mutations appear to be clustered between the argC and metC markers on the host chromosome. They also found that during induction of PBSX, DNA carrying the metC marker is specifically synthesized in multiple copies, which may mean that the prophage DNA replicates in situ with the concomitant amplification of adjacent host markers.…”
Section: Transducing Phages and Pseudolysogenymentioning
confidence: 99%
“…The host that was lysogenized by the wild-type phage from which 4105 DNA was isolated was B. subtilis 168 strain GB75. This strain is noninducible for the defective phage PBSX(33). The 4)105 sus mutants were assayed on strain MB228, which carries the Su+3 suppressor, and 44AO was used as the nonpermissive host.…”
mentioning
confidence: 99%